Measuring the temperature and heating rate of a single ion by imaging - Srivathsan, Bharath; Fischer, Martin; Alber, Lucas; Weber, Markus; Sondermann, Markus; Leuchs, Gerd (New Journal of Physics, 2019)

Shifting the phase of a coherent beam with a 174Yb+ ion: influence of the scattering cross section - Fischer, Martin; Srivathsan, Bharath; Alber, Lucas; Weber, Markus; Sondermann, Markus; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2017)
We discuss and measure the phase shift imposed onto a radially polarized light beam when focusing it onto an Yb ion. In the derivation of the expected phase shifts, we include the properties of the involved atomic levels. Furthermore, we emphasize the importance of the scattering cross section and its relation to the efficiency for coupling the focused light to an atom. The phase shifts found in the experiment are compatible with the expected ones when accounting for known deficiencies of the focusing optics and the motion of the trapped ion at the Doppler limit of laser cooling (Hänsch and Schawlow in Opt Commun 13:68–69, 1975).